2006
DOI: 10.1002/cbic.200600151
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate‐Group Recognition by the Aptamer Domain of the Thiamine Pyrophosphate Sensing Riboswitch

Abstract: Riboswitches are highly structured RNA elements that control gene expression by binding directly to small metabolite molecules. Remarkably, many of these metabolites contain negatively charged phosphate groups that contribute significantly to the binding affinity. An example is the thiamine pyrophosphate-sensing riboswitch in the 5'-untranslated region of the E. coli thiM mRNA. This riboswitch binds, in order of decreasing affinity, to thiamine pyrophosphate (TPP), thiamine monophosphate (TMP), and thiamine, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 39 publications
1
17
0
1
Order By: Relevance
“…S5) for the WT aptamer binding to the substrates thiamine (T) and thiamine monophosphate (TMP). These alternative ligands carry fewer phosphates than TPP and are unable to bind the P4∕5 arm via native, magnesium-mediated contacts (19,(26)(27)(28). Nevertheless, the WT aptamer displayed similar energetic stabilization by either T or TMP, when present at saturating concentrations, as did the A90G aptamer bound to TPP (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…S5) for the WT aptamer binding to the substrates thiamine (T) and thiamine monophosphate (TMP). These alternative ligands carry fewer phosphates than TPP and are unable to bind the P4∕5 arm via native, magnesium-mediated contacts (19,(26)(27)(28). Nevertheless, the WT aptamer displayed similar energetic stabilization by either T or TMP, when present at saturating concentrations, as did the A90G aptamer bound to TPP (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…For instance for the thiamine pyrophosphate (TPP)-sensing riboswitch it was shown that Mg 2+ binding is absolutely required for TPP binding (4) and cannot be replaced by monovalent ions or Ca 2+ (5). The X-ray structure of the thiC TPP-sensing riboswitch from Arabidopsis thaliana bound to TPP reveals that one Mg 2+ -ion chelates oxygen atoms in the pyrophosphate moiety of TPP and links them to the RNA whereas there are two bridging Mg 2+ -ions in the X-ray structure of the thiM TPP-sensing riboswitch from Escherichia coli bound to TPP.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] However, to understand how these RNAs function, analysis of the complete TPP riboswitch with and without its ligand is required. However, the ligand-free structure is difficult to refine by NMR spectroscopy or crystallography.…”
mentioning
confidence: 99%